2010
DOI: 10.1159/000319045
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction following Ligation of the Uterine Arteries Leads to More Severe Glomerulosclerosis after Mesangioproliferative Glomerulonephritis in the Offspring

Abstract: Arterial blood pressure, renal function, and proteinuria after 14 days of GN were not influenced by former IUGR. Conclusion: Ligation of the uterine arteries in the rat leads to more pronounced sclerotic changes in the glomerulus in the offspring suffering from acute GN. This finding supports the hypothesis that former IUGR increases the susceptibility for a more severe course of secondary renal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 72 publications
3
33
0
3
Order By: Relevance
“…Bax can induce cell apoptosis and inactive Bcl-2 by forming heterogenous dimers that coalesce with Bcl-2. [19][20][21] Pham et al suggested that Bcl-2 expression was significantly down-regulated and Bax expression was significantly up-regulated in FGR models, 22,23 which was similar to our results in humans. Results from a previous animal study suggested that the decreased number of nephrons in FGR was not only related to cell apoptosis, but also to the changes in the renin-angiotensinogen system (RAS).…”
Section: Discussionsupporting
confidence: 91%
“…Bax can induce cell apoptosis and inactive Bcl-2 by forming heterogenous dimers that coalesce with Bcl-2. [19][20][21] Pham et al suggested that Bcl-2 expression was significantly down-regulated and Bax expression was significantly up-regulated in FGR models, 22,23 which was similar to our results in humans. Results from a previous animal study suggested that the decreased number of nephrons in FGR was not only related to cell apoptosis, but also to the changes in the renin-angiotensinogen system (RAS).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, human and animal studies demonstrate a programming of inflammatory response subsequent to IUGR [18,19]. In line with these observations, Plank et al highlighted a predisposition of former IUGR animals for renal fibrosis and inflammation with a strikingly upregulation of inflammatory and profibrotic marker [Interleukin-6 (IL-6), tumor necrosis factor α (TNF-α), transforming growth factor β (TGF-β)] and of ECM components (collagen I and collagen IV) [20]. It is intriguing though that pulmonary inflammatory response as a link between perturbed ECM and IUGR has not been addressed so far.…”
Section: Introductionmentioning
confidence: 90%
“…[19][20][21][22][23] This model also induces brain injuries related to intrauterine growth restriction (IUGR) in pups, and also fetal deaths. [21][22][23] It is still used today, especially to study these brain injuries. [21][22][23][24] For this study, 32 female rats were anaesthetised on day 16 of pregnancy by intraperitoneal injection of 2% xylazine (Rompum; Bayer, Puteaux, France) and ketamine (Imalgène; Rhô ne Mérieux, Lyon, France).…”
Section: Animal Modelmentioning
confidence: 99%